Use of an agricultural by-product, nano sized Palm Oil Fuel Ash as a supplementary cementitious material - Wi, K.; Lee, H.; Lim, S.; Song, H.; Hussin, M.; Ismail, Mohamed (Elsevier BV, 2018)
An experimental study was conducted with objectives to find out the properties of nano sized Palm Oil Fuel Ash (nPOFA), which is a by-product of palm oil industry, and its effects on the hydration kinetics. The replacement ratios of nPOFA was set at 0–90%. Mortar and paste specimens containing nPOFA were prepared to study the effects of nPOFA on compressive strength and the microstructure. The results of X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicated that the nPOFA mainly consists of SiO2and its average size is 100–150 nm. There was an increase in compressive strength of mortar specimens by the incorporation of nPOFA. However, more than 40% of nPOFA caused the reduction in compressive strength. As curing age increases, the microstructure of the specimens with nPOFA became denser than the samples without nPOFA due to the refinement of microstructure. The reduction in Ca(OH)2from pozzolanic reaction and the further formation of C-S-H were confirmed by thermogravimetric analysis (TGA), XRD and FT-IR. On this basis, a schematic hydration mechanism of nPOFA in cement matrix was proposed, and it is anticipated that nPOFA could be used as eco-friendly cementitious materials.